Loading...

Two thirds minus two ninths is 4 ninths. Two thirds is 6 ninths. 6 ninths minus 2 ninths is 4 ninths.

Eight minus one and one ninth equals six and eight ninths.

6/9 minus 6/9 = Zero.

five-ninths, 5 _ 9

Firstly, do 11 minus 4 = 7. So, now we have 7 and two ninths, minus five ninths. Much easier, 6 and 6 ninths.

3 6/9 or 3 2/3 or 11/3

8/9 - 6/9 = 2/9

It is: 8/9 minus 5/6 = 1/18

3/9 (three ninths), which can be reduced to 1/3 (one third).

1 and eight ninths

Seven ninths minus four ninths is 1/3.

8/9 minus 7/8 = 1/72

1/3=3/9 (8/9)-(3/9)=5/9

One whole is nine ninths. Nine ninths minus four ninths equals five ninths.

Two thirds is six ninths; six ninths minus four ninths is two ninths.

11 - 6 5/9 = 4.4 recurring (that is, 4.4444..) or 4 and four ninths.

5 ninths

Anything minus itself is zero.

The answer is 5 7/18.

67/9 - 53/9 = 14/9 or 1 and 5/9

104/117 - 18/117 = 86/117

seven ninths

5 ninths. (5/9)

The answer is -3.5

11/6 minus 2/9 is 1 11/18